Effect of a number of plant extracts in the life of beetle Tribolium casteneum (Herbst) and flour Trogoderma granarium (Everts). - Najem Korkees; Ayad Ismaeel; Adnan Mohammed (College of Education for Pure Sciences, 2007)
The effects of six aqueous plant extracts ( Capparis spinosa L., leaves; Olea europea L., leaves; Dianthus chinensis, flowers; Mentha longifolia L., leaves and Melia azedarach, leaves and ripe fruits) were studied on a number of biological aspects of Rusty flour beetle Tribolium casteneum (Herbst.) & Khapra beetle Trogoderma granarium (Everts) . Seven concentrations (%0.5 d.O d.5 ,2.5 ,5 ,7.5 dO) were used for each extract. Different effects on the larval longevity have been seen when using different extracts, concentrations and insects species .This study revealed that the extracts have significant affects on the number of larval instars. Some of them increased the number of moulting significantly as compared with that of control, moulting inhibition factor, therefore, appeared negative in khapra beetle larvae Trogoderma granarium; whereas it was positive in most larval stages of rusty flour beetle Tribolium casteneum. Larvae of rusty-red flour beetle failed to change to pupae stages, thus it remained under the exuvia and died. Also, khapra beetle larvae treated with (M azedarach) leaves and fruits extracts could not change to pupae. Development duration was extended in most khapra beetle treatments due to the increasing of the larval longevity. Treating khapra beetle larvae with plant extracts increased the weight of pupae as compared to controls. Sexual ratio was almost 1: 1 in all treatments.